2018
DOI: 10.1088/1361-6579/aae305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of asymmetric volume conductor modeling on non-invasive fetal ECG extraction

Abstract: Objective: Non-invasive fetal electrocardiography (NI-FECG) shows promise for capturing novel physiological information that may indicate signs of fetal distress. However, significant deterioration in NI-FECG signal quality occurs during the presence of a highly non-conductive layer known as vernix caseosa which forms on the fetal body surface beginning in approximately the 28 th week of gestation. This work investigates asymmetric modeling of vernix caseosa and other maternal-fetal tissues in accordance with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Also, the majority of the study population were multiparous, had an epidural analgesia, and had a vaginal delivery, which may not represent most laboring women in some settings. The results are also limited to term pregnancies, as it is known that a poorly conductive layer (vernix caseosa) forms on the fetal body surface between the 28th and the 34th week of gestation, affecting the quality of TAfECG signals 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the majority of the study population were multiparous, had an epidural analgesia, and had a vaginal delivery, which may not represent most laboring women in some settings. The results are also limited to term pregnancies, as it is known that a poorly conductive layer (vernix caseosa) forms on the fetal body surface between the 28th and the 34th week of gestation, affecting the quality of TAfECG signals 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…The body mapping technique ( Figure 1 ) was used to assess the specific regions of NB skin covered by vernix, which is adopted from previously done research. 17 According to the body mapping technique, the body of newborn is delineated into seven regions those are head, arm (upper limb), chest, back, inguinal, sacrum, and leg (lower limb). The distribution of VC was assessed by observing the NB skin for the presence or absence of vernix immediately after delivery.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Keenan et al showed that volume conductor asymmetry results in significant changes in fECG waveform amplitude and morphology (over 70% errors in the observed T/QRS ratio) [64]. Therefore, this method is most effective in the later stages of pregnancy, especially during the labor [50].…”
Section: Continuous Fetal Monitoring In Clinical Practicementioning
confidence: 99%
“…Besides the benefit of a more objective evaluation, the synthetic data enable modelling of different stages of pregnancy, fetal position based on the fetal vectorcardiogram, pathologic states. Four of the artificial fECG signal generators were introduced by Sameni et al [101], Behar et al [44], [45], Martinek et al [46], and Keenan et al [64]. 2 Despite the advantages provided by synthetic data, they fail to compete with thorough performance evaluations using real data.…”
Section: Se =mentioning
confidence: 99%